Informed design for forms - Wright, Patricia (Information Design Journal, 1981)
This paper seeks to develop a heuristic that can be used by form designers during the design process. This heuristic is based on an analysis of the interaction between the form and those who use it (ie, complete it or adminster it). The interaction is analysed in terms of the cognitive processes involved in dealing with the form (perception, memory, decision making, etc). This analysis also provides a framework for interpreting the available research literature. Detailed consideration of users' requirements shows that a multiplicity of design skills are needed for effective form design. This in turn has implications for the nature of the design process.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTA3NS9pZGouMi4zLTQuMDF3cmk